2007
DOI: 10.1017/s1751731107283879
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial protein meal in diets for growing pigs: effects on protein and energy metabolism

Abstract: This experiment investigated the effects of increasing the dietary content of bacterial protein meal (BPM) on the protein and energy metabolism of pigs from weaning to a live weight of 80 kg. Four litters with four castrated male pigs in each litter were used. The litters were divided into two blocks according to age. One pig from each litter was fed one of the four experimental diets. Soya-bean meal was replaced with BPM on the basis of digestible protein, and the BPM contents in the four diets were 0% (BP0),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The collected urine was analysed for purine base derivatives. These experiments are described in detail and the results of the nitrogen balance studies are reported in Hellwing et al (2005Hellwing et al ( , 2007. The present paper presents data regarding protein turnover rate, purine base derivative excretion patterns, and betweenspecies comparative aspects.…”
Section: Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…The collected urine was analysed for purine base derivatives. These experiments are described in detail and the results of the nitrogen balance studies are reported in Hellwing et al (2005Hellwing et al ( , 2007. The present paper presents data regarding protein turnover rate, purine base derivative excretion patterns, and betweenspecies comparative aspects.…”
Section: Methodsmentioning
confidence: 95%
“…During the balance periods, the animals were housed in metabolic cages in the laboratory at an ambient temperature of 20 -228C and a 12 h light: 12 h dark light cycle. Between the balance periods, the pigs were kept in individual pens in the stable (see Hellwing et al 2007). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations